Influences and mechanisms of phosphate ions onto persulfate activation and organic degradation in water treatment: A review - Li, Ning; Wang, Yanshan; Cheng, Xiaoshuang; Dai, Haoxi; Yan, Beibei; Chen, Guanyi; Hou, Li'an; Wang, Shaobin (Water research (Oxford), 2022)
•The effects and mechanisms of phosphate ions on persulfate (PS) activation are discussed.•Phosphate ions favor to attack asymmetric PMS compared to PDS.•The research directions of phosphate ions in PS-AOPs are proposed. Currently, various strategies have been applied to activate persulfate (PS) for contaminant removal from water. However, the background phosphate ions in water affect PS activation and organic degradation, and the mechanism of their influence on the processes is still controversial. In this review, the possible effects of different phosphate forms (HPO42−, H2PO4−, and PO43−) on PS activation and contaminant degradation were systematically evaluated and summarized. Specifically, HPO42− promotes contaminant degradation in direct peroxymonosulfate (PMS) oxidation and thermal/PMS systems, while it exhibits inhibition to thermal/peroxodisulfate (PDS) and ultraviolet (UV)/PDS systems. Meanwhile, H2PO4− inhibits most oxidation processes based on PMS and PDS, except for non-metal dominated and metal assisted PMS systems. Coexisting HPO42− and H2PO4− could present beneficial effects in thermal, Co2+ and non-metal activated and metal assisted PMS systems. Nevertheless, their inhibitory effects were found in direct PMS oxidation, UV/PMS (or PDS) and metal dominated PMS systems. Generally, phosphate ions inhibit PMS/PDS activation through competing adsorption with PMS or PDS on the solid surface, forming a complex with metal ions, as well as occupying active sites on solid catalysts. In addition, phosphate ions can quench radicals for reduced degradation of contaminants. However, phosphate ions could weaken the bond dissociation energy via combining with PMS and contaminants or form a complex with Co2+, thus displaying a facilitative effect. This review further discusses major challenges and opportunities of PS activation with co-existing phosphates and will provide guidance for better PS utilization in real water treatment practice. [Display omitted]